Meningkatkan Kemampuan Berhitung Dengan Model Problem Based Learning Berbantuan Media Magibinpon - Fatmasari, Diah; Azzahra, Wieline Dewi; Ermawati, Diana (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This research aims to improve the numeracy skills of fourth grade students at SD 1 Wergu Wetan using a problem based learning model assisted by a number line in mathematics subject matter of positive and negative integers. The method used in this research is classroom action research. This classroom action research was carried out in cycles I and cycle II using research instruments in the form of tests and evaluation sheets. This research data collection technique uses interviews, documentation and tests. The data analysis techniques used are quantitative and qualitative methods. The research subjects were all 29 grade IV students at SD 1 Wergu Wetan. The results of the research showed that there was an increase in numeracy skills through tests, the percentage of data obtained in cycle I was 41.37%, increasing in cycle II to 79.31% with very good criteria in cycle II. Improving numeracy skills using a problem based learning model assisted by number lines in positive and negative integer material can increase with the fulfillment of success indicators being declared complete.